2011
DOI: 10.1213/ane.0b013e3182042e56
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Implementation of an Automated System for Logging Clinical Experiences Using an Anesthesia Information Management System

Abstract: The AIMS database is a source of contemporaneous documentation of resident experience that can be queried to generate valid, verifiable case logs. The extent of AIMS adoption by academic anesthesia departments should encourage accreditation organizations to support uploading of AIMS-based case log files to improve accuracy and to decrease the clerical burden on anesthesia residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…Many specialties, including anesthesiology, use case logging systems to track clinical experience, and these logs are used as a surrogate for performance in routine care. 2,3,19 But, case logs do not contain evaluative information regarding clinical performance. Simulation has come to play a major role in technical and non-technical skill evaluations as another means of performance assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many specialties, including anesthesiology, use case logging systems to track clinical experience, and these logs are used as a surrogate for performance in routine care. 2,3,19 But, case logs do not contain evaluative information regarding clinical performance. Simulation has come to play a major role in technical and non-technical skill evaluations as another means of performance assessment.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 However, to our knowledge there are no descriptions of an automated, near-real time performance feedback tool that provides residents and program directors with data on objective clinical performance concerning the quality of patient care that residents deliver. The increasing adoption of electronic record keeping in the perioperative period opens the possibility to develop real time or near-real time process monitoring and feedback systems.…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous investigators have found that Decision Support for Resident OR Assignments ACGME case logs and information derived from AIMS records deviates by at least 5% for the majority of residents. 5 Given the current lack of an automated mechanism to resolve these discrepancies or eliminate them by allowing AIMS records to populate ACGME case logs, we included both sets of metrics within Rhinos' resident profiles. With the current read-only ACGME case-log Web service, this is what is currently feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Automated systems can help alleviate some of the manual data entry required by such a system for anesthesiology residents [4]. Additionally, automated systems have been shown to increase compliance with residency expectations in emergency medicine for the patient care and PBLI competencies [5].…”
Section: Introductionmentioning
confidence: 99%